2006
DOI: 10.1099/mic.0.28861-0
|View full text |Cite
|
Sign up to set email alerts
|

Two novel conjugative plasmids from a single strain of Sulfolobus

Abstract: Two conjugative plasmids (CPs) were isolated and characterized from the same 'Sulfolobus islandicus' strain, SOG2/4. The plasmids were separated from each other and transferred into Sulfolobus solfataricus. One has a high copy number and is not stable (pSOG1) whereas the other has a low copy number and is stably maintained (pSOG2). Plasmid pSOG2 is the first Sulfolobus CP found to have these characteristics. The genomes of both pSOG plasmids have been sequenced and were compared to each other and the available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 93 publications
0
44
1
Order By: Relevance
“…Only a few archaeal conjugation systems have been described, so far only for crenarchaeal species (91,174,217,243,250). An early study reported that Haloferax volcanii bidirectionally translocates chromosomal DNA transfer during conjugation, and large structures (2 mm long and 0.1 mm wide) bridging cells were postulated to mediate transfer (228).…”
Section: Archaeal Systemsmentioning
confidence: 99%
“…Only a few archaeal conjugation systems have been described, so far only for crenarchaeal species (91,174,217,243,250). An early study reported that Haloferax volcanii bidirectionally translocates chromosomal DNA transfer during conjugation, and large structures (2 mm long and 0.1 mm wide) bridging cells were postulated to mediate transfer (228).…”
Section: Archaeal Systemsmentioning
confidence: 99%
“…In the original host, pSOG1 exists at a very low copy number (153). After introduction into S. solfataricus through conjugation, pSOG1 was recovered as a high-copy-number plasmid.…”
Section: Genomic Featuresmentioning
confidence: 99%
“…This protein was first identified in a few cryptic plasmids through genome comparisons and was designated plasmid regulatory protein A (PlrA) (150). Genes encoding homologs of PlrA are also present in some archaeal conjugative plasmids (152,153) and in all known genomes of members of the Sulfolobaceae, including 10 Sulfolobus strains, Metallosphaera sedula, and Acidianus hospitalis. Since this ORF is absent from all other archaeal genomes and genetic elements, the genomic copies of plrA in the Sulfolobaceae are speculated to be derived from cryptic and conjugative plasmids via HGT.…”
Section: Genomic Featuresmentioning
confidence: 99%
See 2 more Smart Citations